Mitochondrial-Derived Reactive Oxygen Species Play a Vital Role in the Salicylic Acid Signaling Pathway in Arabidopsis thaliana - Nie, Shengjun; Yue, Haiyun; Zhou, Jun; Xing, Da (PLOS ONE, 2015)
Plant mitochondria constitute a major source of ROS and are proposed to act as signaling organelles in the orchestration of defense response. At present, the signals generated and then integrated by mitochondria are still limited. Here, fluorescence techniques were used to monitor the events of mitochondria in vivo, as well as the induction of mitochondrial signaling by a natural defensive signal chemical salicylic acid (SA). An inhibition of respiration was observed in isolated mitochondria subjected to SA. The cytochrome reductase activity analysis in isolated mitochondria demonstrated that SA might act directly on the complex III in the respiration chain by inhibiting the activity. With this alteration, a quick burst of mitochondrial ROS (mtROS) was stimulated. SA-induced mtROS caused mitochondrial morphology transition in leaf tissue or protoplasts expressing mitochondria-GFP (43C5) and depolarization of membrane potential. However, the application of AsA, an H2O2 scavenger, significantly prevented both events, indicating that both of them are attributable to ROS accumulation. In parallel, SA-induced mtROS up-regulated AOX1a transcript abundance and this induction was correlated with the disease resistance, whereas AsA-pretreatment interdicted this effect. It is concluded that mitochondria play an essential role in the signaling pathway of SA-induced ROS generation, which possibly provided new insight into the SA-mediated biological processes, including plant defense response.